Impact of Cameraria ohridella infestation on the chemical composition of Aesculus glabra leaves in Dnipro city, Ukraine - Sytnyk, S.; Holoborodko, K.; Lovynska, V.; Palchykov, V.; Ivanko, I.; Khrunyk, Y.; Lakyda, P.; Lakyda, Y.; Vyshnevskyi, A. (Regulatory Mechanisms in Biosystems, 2026)
This study investigated changes in the metabolic profile of Aesculus glabra leaves in response to i n festation by the horse chestnut leaf miner ( Cameraria ohridella ) in Dnipro city, Ukraine. Methanolic leaf extracts from uninfested and infested trees were analyzed using gas chromatography–mass spectrometry (GC–MS). Infestation by C. ohridella was associated with substantial metabolic restructuring, reflected by a marked reduction in the number of detected metabolites from 114 in uninfested leaves to 62 in infested leaves. The most pronounced changes were observed among carbohydrate-related compounds, indicating major alterations in carbon metabolism under herbivory stress. Increased relative abundances of sucrose, trehalose, mannobiose, catechin, and several fatty acid derivatives were detected in infested leaves, wher e as multiple organic acids, terpenoid-related compounds, and sterols decreased in abundance or disappeared entirely. In addition, several metabolites, including quercetin, neophytadiene, monopalmitin, β-sitosterol, and hexatriacontane, were detected exclusively in infested leaves and may be associated with induced stress and defense responses. Conversely, compounds such as chlorogenic acid, α-linolenic acid, and β-tocopherol were detected only in uninfested leaves. The results demonstrate extensive metabolic reorgan i zation of A. glabra leaves under C. ohridella infestation and highlight the potential role of specialized metabolites in herbivory-related stress responses.